유용미생물 처리에 따른 들잔디 재배지의 갈색퍼짐병 병원균 감소와 잔디생육 촉진 효과 - 배은지(Eun-Ji Bae); 전창욱(Chang Wook Cheon); 홍아름(A-Reum Hong); 이광수(Kwang-Soo Lee); 곽연식(Youn-Sig Kwak) (Weed & turfgrass science, 2017)
To prevent large patch disease, caused by Rhizoctonia solani AG-2-2, in zoysiagrass a fungicide, Tebuconazole and three microbial agents Streptomyces sp. Burkholderia sp. and Streptomyces sp. S8 were applied in commercial turfgrass cultivation field in Sanchung, Gyeongnam, Korea. All treatments showed 50% reduced the pathogen population in thatch layer throughout the yearly cultivation period. Not only reduced the pathogen population, Tebuconazole, Streptomyces sp. Burkholderia sp. and Streptomyces sp. S8 treatment also enhanced turfgrass growth, chlorophyll and proline content. Malondialdehyde contents in each treatment was reduced from 6.2~28.9% when compared with the control. Taken together, reduction of pathogen population in soil lowered the disease incidence or severity, and allowed the turfgrass developed as normal condition. The results suggested that the selected microbial agents may use as biological control and growth promotion agents for the Zoysia turfgrass. 들잔디 재배지역에 갈색퍼짐병을 방제하기 위하여 Tebuconazole 약제 및 Streptomyces sp.와 Burkholderia sp. 미생물을 처리하였다. 무처리구에 비해 Tebuconazole 약제 처리구, Streptomyces sp., Burkholderia sp.와 Streptomyces S8 미생물 처리구는 잔디의 생육, 엽록소와 카로티노이드, 프롤린 함량은 유의하게 증가하였며, MDA 함량은 감소하였다. 토양미생물인 Streptomyces sp., Burkholderia sp.와 Streptomyces sp. S8 처리에 따라 갈색퍼짐병 병원균밀도 감소로 갈색퍼짐병의 증상이 완화되어 정상적인 잔디로 생육이 된 것으로 판단되었다. 이러한 결과는 사용된 미생물이 잔디의 생물적 방제와 잔디의 생육 촉진 미생물로 이용될 수 있음을 시사한다.